Knowledge of healthcare professionals about breastfeeding and supplementary feeding - Ana Elisa Ramos; Carmen Viana Ramos; Marize Melo dos Santos; Camila Aparecida Pinheiro Landim Almeida; Maria do Carmo de Carvalho e Martins
ABSTRACT Objective: To analyze the knowledge of breastfeeding (BF) and supplementary feeding (SF) of professionals in the Primary Health Care. Method: Cross-sectional study, with 168 professionals, conducted between June and September 2016. The Kruskal Wallis test was used to compare means of percentage of knowledge about BF and SF, by professional category and contingency testing, for association between variables. Results: From the total of professionals, 39.29% of them demonstrated good knowledge about BF and 2.38% about SF; 74.4% of respondents reported not knowing the program Brazilian Breastfeeding and Feeding Strategy (EAAB - Estratégia Amamenta e Alimenta Brasil). There was a positive association between professionals' level of knowledge about BF and education (p=0.04), occupation (p=0.05) and healthcare in BF (p=0.04). Regarding the level of knowledge about SF, there was association between education (p<0.01) and healthcare in SF (p=0.04). Conclusion: The professionals have greater knowledge about breastfeeding when compared to supplementary feeding.